Citizen Participation Facing the Transparency Challenge - Péterfalvi, Attila (Revue internationale des Gouvernements Ouverts, 2016)
[Extract] In Hungary, one of the most important purposes of the 1989 rule of law revolution was to guarantee the right of everyone to exercise control over their personal data and to have access to public data. As regards the latest Hungarian constitutional reform, the legislature left informational rights basically unchanged, and only the institutional background was transformed. The Hungarian National Authority for Data Protection and Freedom of Information, as the defender of two human rights, is responsible for supervising and defending the right to the protection of personal data and to freedom of information. Its responsibilities include both the state and the business sector. Freedom of information guarantees transparency regarding the activities of public authorities and the spending of public funds. Citizens can only be active participants if they are informed – appropriate information is fundamental to freedom of opinion. As clearly stated by the Hungarian Constitutional Court: ‘without being monitored by its citizens, the state becomes an unaccountable and unpredictable machine, and this is especially dangerous because a non-transparent state represents an increased threat to constitutional rights’. Freedom of information is one of the most sensitive rights in a democracy because the political forces always try to control the flow of information. When in opposition, politicians seek greater openness and transparency. When they are in power, they like to control the flow of information to their own advantage. In the field of data protection, the Hungarian DP&FOI Commission controls both the public and private sector since 1995. However, the obligation to safeguard FOI applies to the entire state administration from the municipalities to highest state organs. From the beginning, there was a gap in enforcement regarding publicity of public funds, because, for example, the contracting private party did not have to assure the publicity of the contractual relationship.